POLITICAL DISTRUST AND INTENTION TO MIGRATE ABROAD: AN EMPIRICAL STUDY OF YOUTH IN SOUTH-EAST OF NIGERIA - Onyeke, Paul C. (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2022)
There is a growing concern about the ever-increasing intention of people to relocate to other countries. The trend is pervasive among young individuals and creates the path for illegal migration and burdens immigration policies. Although much has been documented about migration motives, little is known about the contribution of political distrust in emigration. The present paper investigated young people's intention to migrate abroad based on political distrust. Six hundred and fifteen youth were conveniently pooled from different locations in southeast Nigeria for the survey.